^1^2 • • • M(v-1) / v 2 -(M1M2 • • • M(v-1))d(v-1)) with the condition v > 1 In these formulae the following quantities are pre-defined:
Because of the singularity, apart from the case of y1, the formulae break down for v = 1. The recursive nature requires = +1, but the specific case of v =1 gives = 0, which also gives the correct result from the terms — 1) and + 1) for A1 and A ( vn) 1.
For a 4-mirror telescope working in the normal way with s1 = ro, the formulae (3.335) then give the following results, in which = +1 by definition:
Was this article helpful?